PENGEMBANGAN PENDIDIKAN KARAKTER BERBASIS KEARIFAN LOKAL PADA MASYARAKAT MINORITAS ( Studi atas Kearifan Lokal Masyarakat Adat Suku Baduy Banten) - Hasanah, Aan (Analisis: Jurnal Studi Keislaman, 2012)
The nation’s  character  is built from the core ethical values derived from the values of religion, philosophy and culture of the State. The values derived from national cultures are in  great quantities and of highly diverse and contain  lofty  values of the country which enable this nation  a strong  social capital  possession  in building   superior civilization. In reality, however, such lofty values of national cultures, experiencing many challenges, due to the rush out of external values and step in the original values of our national cultures. Local wisdoms in many groups of / minority communities in Indonesia have been often overlooked,  whereas, these local wisdoms can actually be promoted to become a model for developing   the character education-based  on Indonesia’s character of origins. By the use of  cultural-anthropology approach,   this  paper   tries  to  uncover   local  wisdom   values   on indigenous  Bedouin  people  of Banten  as a defining characters,  i.e. environmental  care, love to work hard, obedient  to law /customary law, a simplicity /independent, democratic, hard-working and uphold honesty. These values, in line with author’s research findings actually to be internalized  and  preserved  among  indigenous  peoples,  to be taught, socialized, exemplified and enforced strictly by the rules, so as to form a strong character.